A Systematic Mapping of Teaching and Learning Using Educational Robotics in Brazilian Basic Education - Rezende, Críscilla; Inocêncio, Ana Carolina; Oliveira, Thiago; Boaventura, Ana Paula (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
This paper presents the results of a systematic mapping that investigated what concepts can be taught with educational robotics, aiming to guide the development of didactic kits focused on the teaching of exact sciences for Brazilian Basic Education. We correlated and presented the results using the terminology adopted by the Currículo Referência da Rede Estadual de Educação de Goiás. The analysis showed that the use of robotics to teach mathematics concepts is more emphatic, although contents related to physics, chemistry, and science were also found. Was verified in this systematic mapping that the use of educational robotics contributes positively as a mediator in the teaching-learning process of exact sciences. Through the text, are also described many possibilities of application.